Comparative characterization of Upper-Pleistocene and modern day coral skeleton - Ferreira, Paulina Rossi (2023)
Reefs are marine formations with biological, ecological and scientific value, such as harboring enormous biodiversity, protecting the shoreline from waves and marking sea-level and sea temperature evolution through epochs. Corals thrive in a variety of habitats according to their adaptations, having colonized depths from 0 to 2000 m from the sea surface and all latitudes across Earth. Reefs are mainly constituted by scleractinian corals, also known as stony corals, that synthesize a calcareous skeleton which act as scaffold for other organisms to shelter. The synthesized limestone captures carbon and performs an important role in Oceans carbon cycle as carbon sinks. Since the decade of 1950, scleractinian corals are known for depositing aragonite which is a metastable calcium carbonate polymorph with rare natural occurrence, being calcite the most stable polymorph. Coral aragonite have shown interesting physical properties such as distorted aragonite unit cells and different phase transition temperatures when compared to geological aragonite, also notable mechanical strength capable of enduring oceanic tides. This work studies two colonial corals found in brazilian fauna for their age, chemical composition, crystalline structure and thermal behavior. Assessed specimens are Mussismilia hispida (Verrill, 1901) collected at 10 m deep and Lophelia pertusa (Linnaeus, 1758) collected 852 m deep, called Mh and Lp respectively. Results from radiocarbon dating tell that Mh is 22 years old modern coral and Lp is 12000 years old fossilized Pleistocene corals. Both samples are composed of aragonite and present trace elements originated in seawater, such as Mg, Na, Sr, S and Cl. Their thermal behavior and phase transition temperatures were proven to be distinct from other scleractinian corals previously studied. Although all corals presented the beginning of phase transition at 285 ºC, our samples ended the process 310 ºC, 100 ºC cooler than the model corals, around 400 ºC. This phenomenon is reputed to corals being of different clades, hence having a fundamental genetic difference, but this has to be studied further.